Macrozoobenthos Community Structure as a Bioindicator for Waters in Sungai Kakap Village, Kubu Raya - Marista, Etha; Raynaldo, Adityo; Shofiyah, Sofi Siti; Zibar, Zan; Saputra, Robin; Linda, Riza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Coastal waters are vital for aquatic life and human activities, yet their quality is highly susceptible to environmental pressures. Because macrozoobenthos are sensitive to environmental changes and have limited mobility, they are frequently utilized as bioindicators. This study aims to examine the structure of the macrozoobenthos community in the waters of Sungai Kakap Village, Kubu Raya Regency, and its relationship with environmental parameters. Samples were collected at five stations using purposive sampling with line transects and quadrants, then analyzed for density, diversity (H'), evenness (E), and dominance (C). A total of 14 species were found with distinct dominant patterns across stations, notably the high dominance of Neritina violacea, Corbicula fluminea, and Corbicula fluvitalis at Stations I, III, and V, respectively. Community structure analysis showed low diversity (H': 0.33–0.65) and high dominance (C: up to 0.84), suggesting a community structure dominated by a few species, leading to relatively low stability. Environmental parameters—temperature (30.1–31.7∘ C), salinity (0.50–3.00%), pH (5.45–7.58), and DO (3.77–7.51 mg/L)—were found to influence species distribution. These results confirm that macrozoobenthos is an effective bioindicator for water quality assessment in the Sungai Kakap area. The low community stability implies a need for consistent monitoring to prevent further degradation. Future research should focus on the impact of specific pollutants on these dominant species to support informed mangrove ecosystem management.